Characterization of Bacillus thuringiensis isolat from several areas in Java and South Sulawesi for biological control of myasis, Chrysomya bezziana - S Muharsini; April H Wardhana; H Rijzaani; B Amirhusein (Indonesian Center for Animal Research and Development (ICARD), 2003)
Bacillus thuringiensis is a species of bacteria which has potential use for biological control of parasite. The aim of the study is to characterize the local isolate of B. thuringiensis using PCR technique. Primer of cry gen was used in the study. Two hundred and twenty seven soil samples were collected from several areas in Java Island and South Sulawesi Province. Samples were obtained from surrounding soils of animal housing and paddocks. Samples were inoculated in Nutrient Agar and the suspect of bacilli were then cultured in Luria Bertani acetic buffer. Seventy-three pure isolates of Bacillus thuringiensis were obtained. Thirty-five isolates from Bogor, Yogyakarta and Majalengka regencies were amplified using PCR and consisted of a B. thuringiensis sporulation gene which has a 850 bp band in an agarose gel. Amplification using cryIVA,B primers demonstrated four isolates contain a faint band of 800 bp and 12 isolates consist of a distinctive band of 300-400 bp. The results showed that several B. thuringiensis isolates containing a cry IV gen and those isolates are needed to be tested as a biological control agent for Chrysomya bezziana. Key words: Bacillus thuringiensis, Chrysomya bezziana, biological control, cry IV gen